Ocular Biometry and Corneal Astigmatism in Patients Undergoing Cataract Surgery in Bheri Zone of Nepal - Thapa, Bikram Bahadur; Dhakal, Y.; Verma, J. K.; Manandhar, P. (Journal of Nepalgunj Medical College, 2017)
Introduction: Accurate measurement of ocular axial length, keratometry and anterior chamber depth before cataract surgery is crucial for calculating the power of intraocular lens (IOL) to be implanted. Corneal astigmatism is one of the major thefts to have best postoperative unaided visual acuity. Thus, knowing it preoperatively and taking appropriate intervention during surgery provides best postoperative visual outcome. But there are no studies on corneal astigmatism and biometric parameters in the population of Bheri Zone. MATERIAL AND METHOD: The medical records of the patients who had ndergone cataract surgery between January 2017 and November 2017 at Nepalgunj medical college were retrospectively reviewed and analyzed. Patient's demographic parameter, keratometric value, anterior chamber depth, lens thickness and axial length data were collected and analyzed. RESULTS: This study evaluated the data in 65 eyes of 65 patients who had undergone cataract surgery. The mean age of patients was 59.3 ± 15.71 years. The mean corneal astigmatism was 1.37 D ±1.4D (range 0.00-6.75D). Corneal astigmatism was higher than 1.00 D in 32.3% of cases. The mean average keratometry was 44.54±1.83D. The magnitude of corneal astigmatism was positively correlated with age (p<0. 001) and there was a tendency for corneal astigmatism to increase with age above 50 years. Against-the-rule regular astigmatism was the most common type (46.2%) of astigmatism observed in this study. CONCLUSION: The present report showed the pattern of corneal astigmatism before cataract surgery in the patients at Nepalgunj Medical College Teaching Hospital. One third of cataract patients had corneal astigmatism of more than 1.0D. This finding provide the important normative reference and help ophthalmologists to plan and manage the cost-effective correction of preexisting corneal astigmatism in cataract patients to achieve the best visual outcome.